2022
DOI: 10.3390/cryst12020157
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Response of As-Cast CoCrFeNi and CoCrFeMnNi High-Entropy Alloys

Abstract: In this research, we systematically investigated equiatomic CoCrFeNi and CoCrFeMnNi high-entropy alloys (HEAs). Both of these HEA systems are single-phase, face-centered-cubic (FCC) structures. Specifically, we examined the tensile response in as-cast quaternary CoCrFeNi and quinary CoCrFeMnNi HEAs at room temperature. Compared to CoCrFeNi HEA, the elongation of CoCrFeMnNi HEA was 14% lower, but the yield strength and ultimate tensile strength were increased by 17% and 6%, respectively. The direct real-time ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…By tensile and compression tests, many reports illustrate that FCC HEAs possess an excellent plastic deformation ability. Lam et al [ 24 ] reported that CoCrFeNi HEA undergoes step loading in an elastic state and is then subjected to continuous loading at a nominal strain rate of 5 × 10 −5 s −1 ; it had elongation to failure of 107%. Stepanov et al [ 25 ] found that CoCrFeMnNi HEA had excellent ductility and could be compressed to a height of 75% without fracture.…”
Section: Introductionmentioning
confidence: 99%
“…By tensile and compression tests, many reports illustrate that FCC HEAs possess an excellent plastic deformation ability. Lam et al [ 24 ] reported that CoCrFeNi HEA undergoes step loading in an elastic state and is then subjected to continuous loading at a nominal strain rate of 5 × 10 −5 s −1 ; it had elongation to failure of 107%. Stepanov et al [ 25 ] found that CoCrFeMnNi HEA had excellent ductility and could be compressed to a height of 75% without fracture.…”
Section: Introductionmentioning
confidence: 99%
“…High entropy composites have been developed by vacuum arc melting 44 , mechanical alloying 45 48 , 52 , 53 , spark plasma sintering 46 , 51 , 52 , vacuum hot pressing 45 , hot iso-static pressing 47 , 48 and additive manufacturing 43 , 50 processes. Carbides, oxides and nitrides such as WC 44 46 , Al 2 O 3 47 , SiC 48 , TiC 43 , 49 , TiN 50 and Y 2 O 3 51 have been used as ceramic reinforcement for the development of HEA composites. Selection of a suitable HEA matrix and ceramic phase is particularly important to design and develop strong and tough HEA composites.…”
Section: Introductionmentioning
confidence: 99%
“…This system has rapid strain hardening characteristic 44 and excellent ductility both at cryogenic and elevated temperatures 45,46 . Different attempts have been made to improve its relatively lower strength (~ 300 MPa) 47,48 , which include grain refinement 25 , multiphase microstructure 49 , precipitation [50][51][52] , and transformation induced plasticity (TRIP) 53 . Grain refinement of the as-cast fcc CoCrFeNi HEA by heavy cold-drawing resulted in an increased strength from ~ 300 MPa 47,48 to 1.2 GPa 25 , but with a loss of ductility from more than 60% to 12.6%.…”
mentioning
confidence: 99%
See 2 more Smart Citations